Effectiveness of the Team Games Tournament Model Assisted by Photomath Interactive Learning Media - Anjani Aprilia; Ria Faulina (FKIP Universitas Halu Oleo, 2024)
Education as a human effort to grow and develop talents and potentials that are owned from birth. To understand science, mathematics education needs to be mastered by students to help them digest the sciences that will come later at a higher level. Based on data released by Worldtop20.org, Indonesia's education ranking in 2023 is ranked 67th out of 203 countries in the world, this shows that interest in learning in Indonesia is still relatively low. This study aims to determine the effectiveness of the TGT (Team Games Tournament) model assisted by Photomath interactive learning media on Algebra material. The results of descriptive statistics show that the application of the TGT (Team Games Tournament) learning model assisted by Photomath interactive learning media on Algebra material has met the indicators of completeness. It can be concluded that math learning is efficient from the implementation of the TGT (Team Games Tournament) model assisted by Photomath interactive learning media on Algebra material in class VII-A SMP Negeri 1 Socah which is observed through student learning outcomes, student responses, and student activities. This can be seen through the results of data analysis which overall reached a value of ≥75 or can be said to exceed the target set.